Analisis Unsur Fisik Dan Batin Pantun Balas -Berbalas Pada Saat Kegiatan Nampun Kule Adat Asli Suku Pasemah - Aprilia, Heni; Khermarinah, Khermarinah; Sari, Wenny Aulia (Lembaga Riset dan Inovasi Almatani, 2024)
The pantun tradition in the Nampun Kule (Proposal) activity in Air Mayan Village, Pasemah Air Keruh District has an important value as a communication medium, which conveys advice, moral messages, and strengthens social and cultural ties. However, along with the development of the era and modernization, the use of pantun in Nampun Kule has begun to decrease. The younger generation is increasingly losing interest in this tradition, so that the preservation of this oral culture faces a major challenge. This raises concerns about the extinction of the pantun tradition as part of the cultural identity of the Pasemah tribe. This study aims to analyze the physical and spiritual elements of pantun in the Nampun Kule activity of the Pasemah tribe in Air Mayan Village, Kampung 7 Air Ringkeh, Pasemah Air Keruh District. This study uses a qualitative descriptive method with data collection through observation, in-depth interviews, and documentation. The research sources consisted of the traditional leader, the head of the hamlet, the head of the imam, and representatives of the community. The research instruments include interview and observation guidelines. The results of the study show that pantun in Nampun Kule has its own characteristics. In addition to functioning as entertainment, these pantuns also convey moral and spiritual messages, such as hopes for happiness, harmony, and life advice for the bride and groom. Although this tradition has experienced a decline in use due to modernization, the people of Air Mayan Village still maintain pantun as part of their cultural identity. This study contributes to the preservation of traditional culture, especially pantun in Nampun Kule activities, as well as enriching the study of oral arts and culture in Indonesia